Complex coacervation and metal–ligand bonding as synergistic design elements for aqueous viscoelastic materials. Issue 12 (3rd March 2021) - Filippov, Alexei D.; Sprakel, Joris; Kamperman, Marleen
Abstract : Metal-ligand bonds work together with a pair of oppositely charged polyelectrolytes to extend the viscoelastic repertoire of complex coacervates. Abstract : The application of complex coacervates in promising areas such as coatings and surgical glues requires a tight control of their viscous and elastic behaviour, and a keen understanding of the corresponding microscopic mechanisms. While the viscous, or dissipative, aspect is crucial at pre-setting times and in preventing detachment, elasticity at long waiting times and low strain rates is crucial to sustain a load-bearing joints. The independent tailoring of dissipative and elastic properties proves to be a major challenge that can not be addressed adequately by the complex coacervate motif by itself. We propose a versatile model of complex coacervates with customizable rheological fates by functionalization of polyelectrolytes with terpyridines, which provide transient crosslinks through complexation with metals. We show that the rheology of the hybrid complexes shows distinct footprints of both metal–ligand and coacervate dynamics, the former as a contribution very close to pure Maxwell viscoelasticity, the latter approaching a sticky Rouse fluid. Strikingly, when the contribution of metal–ligand bonds is dominant at long times, the relaxation of the overall complex is much slower than either the "native" coacervate relaxation time or the dissociation time of a comparable non-coacervate polyelectrolyte–metal–ligand complex. We recognize this slowing-down of transient bonds as a synergistic effect that has important implications for the use of complementary transient bonding in coacervate complexes.